Issak Omnibus. 1 - Makari, Shinji (Kodansha Comics, 2025)
The year is A.D. 1620. Europe is riven with the conflagrations that will grow into the Thirty Years War. Catholic and Protestant forces clash across battlefields ruled by sword and gunpowder alike, and mercenaries of every stripe ply their trade. Among them is Issak, a lone Japanese warrior wielding a matchlock gun of strange design, on a sworn mission to find and kill the man who murdered his master and fled Japan for the other side of the world.